A study of establishing WBV's profile for bus drivers along Road from East to West Coast of Malaysia - Siti Norazarina, Razali (2012)
Many bus drivers are exposed to health risks, due to repeated exposure to vibration and noise. Vibration arises when a body moves back and forth or oscillates due to internal and external forces then it can be transmitted to the human body such as leg and arms but most commonly through the buttocks while seated in the vehicle. The vibration energy can be passed through the part in contact with the vibrating surface like the seat of the mobile machine, vehicles on rough roads, or vibrating tools. Noise termed as unwanted or undesirable sound, which effects in our living and working environment. Noise levels can be affected by a number of variables, including elevation, terrain, distance from the source, and weather. In addition, noise level's decrease with distance from a noise source. The change in noise level depends on the type of terrain, as well as the type of source. Weather conditions alter both noise levels and the transmission of noise from a source to where it is received. This paper presents recent results from an investigation of vibrations and noise, which imposed on the bus driver from the road along Kuantan to Kuala Lumpur. The vibrations have been evaluated in accordance with the new standard ISO 2631-1:1997. Meanwhile, noise is compared with OSHA Permissible Noise Exposure. 20 subjects completed a questionnaire regarding their general health, and specifically whether they experienced low back pain and if so, the extent and severity of this pain. It was expected that the individuals subject to the highest vibration levels would tend to report LBP, with severity of pain increasing with the intensity of exposure. This study did not support that belief. However, it may be that chronic exposure to whole-body vibration is a stronger predictor than daily expose levels. In conclusion, bus drivers should pay particular attention to safety and security of the driver and where circumstances are particularly difficult use, two people operated buses and if needed stop for a short break before continue the journey. Therefore, it is required that more research should be conducted in various transportation sectors in Malaysia to emphasize the effect of whole-body vibrations and noise to the driver.